Electronic contract formation: global harmonization or local variation? - with special reference to sri lanka - Sumanadasa, W.A.D.J. (University of Jaffna, 2012)
In recent years, with the dawn of peace in the country, the promotion of investments and businesses has taken priority in the development drive of the post-war Sri Lanka. In that context, it is undeniable that the reliance on information and communication technology is inevitable. Moreover, electronic-contracts have gained importance in our daily life over last decades. Even more interestingly, in the world of growing Internet, electronic transactions seem to depict not only a phenomenal success of the new technology, but also a conceptual puzzle that challenges conventional wisdom on legal principles. However, limited academic attention has been paid to investigate the issues posed by e-commerce contracts not only in Sri Lanka but also in many jurisdictions. The traditional law relating to formation of contract seems to be not directly applicable for contracts that are entered into online in the era of rapid development of information technology and improvement thereof. Even the introduced e-commerce model laws do not provide clear-cut solutions for neo-native issues such as mobile electronic commerce. There is also a challenge to the validity of the orthodox concepts of contract law relating to the formation of contracts such as offer and acceptance, capacity to the contract and other formalities in the world of growing e-commerce transactions. In this backdrop, this research attempts to analyze the issue of novel application of electronic contract law in the context of the ‘old wine in new bottles’ and to come up with possible recommendations. Moreover, this research deals with the identification of possible solutions for the traced problems in the existing legal framework. It is hoped that this research would be a stepping stone for law reformers, practitioners, adjudicators and academics in their attempts to expand the horizons of the application of contact law in a digital era.